A study of synthetic lignin decolorization ability of P. chrysosporium, T. hirsuta and marine fungi - Basavapunnaiah Naidu; Ranga Reddy; Rao Koratala Satyanarayana; Venkayya Prakasam (African Journal of Environmental Economics and Management, 2014)
Lignin is an organic compound abundantly found in wood. Degradation of lignin poses major problems for paper mill industries all over the world with regard to the dark- brown color of lignin in wastewater, which is also a major problem facing the environment today. The decolourization capability was tested with species like Phanerocheate chrysosporium, Trametes hirsuta and an isolated native Marine fungi – M1 using synthetic lignin. The result showed that, isolated strain decreased the lignin color by up to 20% after cultivation for 7 days. Where the decolourisation ability of the fungi Phanerocheate chrysosporium and Trametes hirsuta was observed to 80 and 70% respectively.